2020
DOI: 10.1177/2378023120942070
|View full text |Cite
|
Sign up to set email alerts
|

Health Lifestyles and the Transition to Adulthood

Abstract: Prior research has shown the theoretical importance and empirical feasibility of health lifestyles but has not examined their patterns over the life course or their dynamic associations with socioeconomic status (SES) and adult roles. The authors develop and apply a life-course approach to understanding individuals’ health lifestyles across the transition to adulthood, using U.S. data from the National Longitudinal Study of Adolescent to Adult Health ( n = 6,863). The results show that ascribed SES is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 63 publications
(96 reference statements)
3
29
0
Order By: Relevance
“…All analyses are stratified by gender because women are generally found to have healthier lifestyles than men. [32][33][34]37 All analyses were conducted in Stata 16, using 25 imputed data sets and reporting the average parameter estimates across all the complete data sets along with corrected SEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All analyses are stratified by gender because women are generally found to have healthier lifestyles than men. [32][33][34]37 All analyses were conducted in Stata 16, using 25 imputed data sets and reporting the average parameter estimates across all the complete data sets along with corrected SEs.…”
Section: Discussionmentioning
confidence: 99%
“…Most past research on health lifestyles has focused on earlier stages of the life course and assumed that health lifestyles formed in adolescence and young adulthood persist later in life. [33][34][35][36] The finding of a general lack of healthier lifestyles in late-middle age in this sample of Black Americans suggests the possibility of less healthy lifestyles at earlier ages, which could in part reflect lifelong exposures to stress and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Class circumstances or SES establish the catalog of options available for the individual to choose from and the rank order of preferences for the individual. Consequently, class circumstances are the key structural variable in determining health lifestyle patterns (Carpiano, Link, and Phelan 2008; Christensen and Carpiano 2014; Cockerham 2005, 2021; Lawrence et al 2020; Mollborn and Modile 2022; Rees Jones et al 2011; van den Broek 2021).…”
Section: Updated/expanded Modelmentioning
confidence: 99%
“…Scholars have found that lived experiences in late adolescence and early adulthood have more influence in the construction and reconstruction of young people's gender ideology than social and background origins (Davis 2007). Given the fact that the transition to adulthood is a long process in the United States, something emphasized by the literature on the life course (Arnett 2004;Lawrence et al 2020), we include traditionalaged college students in this study as an older group of adolescents whose gender ideology is still in flux but is nonetheless significant.…”
Section: Original Articlementioning
confidence: 99%